Barents-Kara sea-ice decline attributed to surface warming in the Gulf Stream - Yoko Yamagami; Masahiro Watanabe; Masato Mori; Jun Ono (Nature Communications, 2022)
Climate model simulations show that for 1970-2017 externally-forced sea surface temperature increases in the Gulf Stream explain up to 56% of the sea-ice decline in the Barents-Kara Sea during winter via poleward oceanic heat transport.